Management of Student Engagement: A Matrix Consolidated - Dickie, Carolyn; Kayani, Amina; Dickie, Laurence (The Academy of World Business, Marketing, and Management Development, 2010)
Student engagement has been characterized in literature by a myriad of meanings and a complicated set of research results that are difficult to compare because definitions are often re-configured from one study to the next. Though considered to be an important precursor to student learning and predictor of student achievement, few researchers have attempted to consolidate a reliable measure of student engagement. We approached the concept of engagement through the exclusive lens of the students and, consequently, consolidated a condensed form of the 'Student Engagement Matrix' encompassing the most relevant engagement factors based on a sample of second year International Business Studies Students at different campuses of a university. The objective was to develop a relevant standardized matrix that could be used as a measure to identify the level of engagement across students with different demographic characteristics. Future research is required to validate the measure; once validated, the matrix could be used to benchmark achievement of unit outcomes amongst university students.